RELIGIOUS ROOTS OF THE CASAMANCE CONFLICT AND FINDING A PATH TOWARDS ITS RESOLUTION - Baum,Robert (2021)
Abstract This article examines the root causes of the Casamance conflict, focusing on issues related to the religious significance of the land. Understanding this dimension of the conflict is essential for the achievement of a peaceful settlement. It begins with a brief discussion of geographical, historical, cultural, and political factors. While rejecting a sectarian approach to religious aspects of Diola secessionism, I examine religious dimensions of land, property rights, and conflicts over the land. These became particularly intense after the abrogation of Diola property law in 1978 and the nationalization of land throughout Senegal. This threatened a sense of Diola autonomy as well the religious basis of understanding Diola property law and conflict resolution. The article concludes with a discussion of some of the difficulties of incorporating Diola land law into a local Casamance legal process.